Innovative Strategies in Revitalizing Islamic Education: Case Studies in Pesantren as a Model of Community Empowerment - Saputro, Muhamad Rikza; Sukiman, Sukiman (International Journal of Social Service and Research, 2024)
This research delves into the pressing challenges faced by Indonesia's education system in preparing the younger generation for global demands, amidst issues like lawlessness and social conflicts. Focusing on the revitalization of Islamic Religious Education, particularly within pesantren (Islamic Boarding Schools), the study employs a Systematic Literature Review (SLR) methodology to analyze existing literature. The findings underscore the need for holistic development in faith, morals, ethics, intelligence, and skills within Islamic education. The study identifies innovative strategies, including personnel standardization, contextualized learning materials, positive habitat creation, and cultivating students' passion for learning. These insights contribute to the enhancement of Islamic education within pesantren, aiming to equip the younger generation with the skills and knowledge necessary to confidently face global challenges in the future.